2020
DOI: 10.7759/cureus.c27
|View full text |Cite
|
Sign up to set email alerts
|

Correction

Abstract: ObjectiveCoronary artery disease (CAD) constitutes a significant health hazard in middle-aged individuals in Saudi Arabia. We sought to assess the level of knowledge of cardiovascular risk factors and describe the perception of coronary intervention among the general population in the city of Jeddah in the western part of Saudi Arabia. MethodsA cross-sectional study was conducted in the city of Jeddah during the period from April 2019 to September 1, 2019, by using a structured online questionnaire to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…The knowledge deficit that diabetes and chronic kidney disease were not considered as serious factors in causing CVD might explain the high prevalence and lack of control of these two risks. Similar findings were reported with a negative dietary intake being the highest risk factor, and only 12%, 26%, and 39% of the sample indicated that diabetes mellitus, smoking, and lack of physical activity were risk factors for CVD, respectively [2]. Although most participants were familiar with the most known CVD risk factors, the majority could not correctly identify all the risk factors.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The knowledge deficit that diabetes and chronic kidney disease were not considered as serious factors in causing CVD might explain the high prevalence and lack of control of these two risks. Similar findings were reported with a negative dietary intake being the highest risk factor, and only 12%, 26%, and 39% of the sample indicated that diabetes mellitus, smoking, and lack of physical activity were risk factors for CVD, respectively [2]. Although most participants were familiar with the most known CVD risk factors, the majority could not correctly identify all the risk factors.…”
Section: Discussionsupporting
confidence: 74%
“…In the current study, the majority (87.6%) indicated chest pain or discomfort as the most prominent symptom, higher than reported in studies from Kuwait and Saudi Arabia [2,16]. Being knowledgeable about CVD signs and symptoms is important, supporting early intervention and a better outcome.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation